2017
DOI: 10.1016/j.fcr.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth patterns in a tripartite strip relay intercrop are shaped by asymmetric aboveground competition

Abstract: Intercropping is a promising model for ecological intensification of modern agriculture. Little information is available on how species growth patterns are affected by size-asymmetric above-and belowground competitive interactions, especially in intercrops with more than two species. We studied plant growth and competitive interactions in a novel intercropping system with three species: wheat, watermelon and maize. Wheat and maize are grown sequentially (as a double cropping system) in narrow strips while wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The asymmetric competition is the unequal distributions of available resources between component crops: the crops at the top of a competitive hierarchy can access and obtain more available resources than the one at the bottom (Freckleton & Watkinson, 2001;Weiner, 1990). However, it is unclear how size-asymmetric competition affects the aboveground and belowground interspecific interaction in intercropping (Huang et al, 2017). In MSRI, when soybean emerges, the soybean seedlings come under maize shade and receive fever nutrients, light and water for its growth and development (Feng et al, 2019;Raza, Khalid, Zhang, Feng, et al, 2019).…”
Section: Plant Growth As Affected By Interspecific Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The asymmetric competition is the unequal distributions of available resources between component crops: the crops at the top of a competitive hierarchy can access and obtain more available resources than the one at the bottom (Freckleton & Watkinson, 2001;Weiner, 1990). However, it is unclear how size-asymmetric competition affects the aboveground and belowground interspecific interaction in intercropping (Huang et al, 2017). In MSRI, when soybean emerges, the soybean seedlings come under maize shade and receive fever nutrients, light and water for its growth and development (Feng et al, 2019;Raza, Khalid, Zhang, Feng, et al, 2019).…”
Section: Plant Growth As Affected By Interspecific Interactionsmentioning
confidence: 99%
“…The competition among two crop species is closely associated with the supply of resources and allocation (Craine & Dybzinski, 2013;Liu et al, 2016), size of the plants (Park, Benjamin, & Watkinson, 2003), and spatial and temporal arrangements of components (Xie & Kristensen, 2017;Yang, Qing, et al, 2017). Since these factors affect the initial size of the plant, thus, initial plant size advantage mainly causes the competition between two species (Huang et al, 2017;Schwinning & Weiner, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, maize-soybean relay-strip intercropping is widely adopted in southwestern parts of China, where maize is sown in April and harvested in August, while soybean is sown in June and harvested in October[ 2 ]. The advantages of this system include the effective and efficient utilization of farmland resources[ 3 ] and low incidences of diseases, pests, and weed damage[ 4 , 5 ]. This system also increases the economic benefits compared with that of sole cropping of soybean[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In past reports it has been reported that the shading condition significantly changed the morphological characteristics, biomass, and physiological response of soybean seedlings [ 23 , 14 ]. Several studies have also provided insights into the leaf anatomical features of various plants under shading conditions [ 24 , 21 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, double cropping systems are important factors that influence cotton growth and yield components [6]. Owing to the indeterminate growth habit of cotton plants, cotton crops display morphological adaptations to their growth environment, including modifications to their canopy structure in response to planting patterns [7–10]. Morphological adaptations with respect to canopy development, light interception, source-sink relationships and assimilate partitioning are the major determinants of lint yield [1112].…”
Section: Introductionmentioning
confidence: 99%